Poland: Ineffectiveness of Legislation in Defeating the Demographic Crisis - Andrzejewski, Marek (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
The author presents the regulations of Polish law and considers whether they can affect the procreative decisions of both Polish men and women. For the past almost thirty years, the reproductive rate in Poland has not exceeded1.5, while replacement of generations can be achieved at a rate of 2.1 children per woman of childbearing age. The demographic crisis is the biggest social policy problem in Poland today. Analysing the current law, the author reflects on possible solutions in the future, also referring to solutions that have been abandoned but were in force earlier. He supports all considerations with data drawn from the Population Census conducted in Poland in 2021, the Demographic Yearbook of the Central Statistical Office for 2022, and demographic literature. He places the greatest emphasis on the analysis of family laws, especially marriage and divorce regulations since demographers see a correlation between these regulations and procreation decisions. However, the correlation seems to be small. The conclusions drawn are disappointing; the disappointment applies both to the assessment of the lack of influence of family law regulations on procreation decisions and social law. The latter has recently undergone significant changes in Poland and they were aimed at ensuring economic stability for the family after the birth of a child. Moreover, no connection between the abortion ban and the increase in births has been found. In fact, a sharp decline in births occurred when the abortion ban was introduced. Besides, the introduction in 2015 of the law allowing in vitro procedures did not improve the poor demographic situation either.Keywords: Demography, family law, marriage, divorce, abortion, artificial procreation, social law, social policy